Effect of Scaffolding Instructional Strategies on Pupils’ Attitude to Basic Science and Technology in Rivers State, Nigeria - , Ejekwu, Princewill Okechukwu (Archives of Current Research International, 2020)
This study examined the effect of scaffolding instructional strategies on pupils’ attitude to Basic Science and Technology in public primary schools in Rivers State. Four purpose and four null hypotheses guided the study. Non-randomized pretest, posttest control group experimental design was adopted for the study. The population consisted of 42,409 basic four pupils; 147 pupils in the intact classes of the sampled schools using simple random sampling technique served as sample. The modified Fennema-Sherman Attitude Scale was used for data collection. The data was analyzed using Analysis of Covariance (ANCOVA). The findings of the study revealed that there is a significant difference in the Basic Science attitude mean score of pupils taught with modeling and cueing questions and those taught with conventional method; the Basic Science attitude mean scores of boys and girls, high achievers and low achievers taught with modeling and cueing questions do not differ significantly with those taught with conventional method; there is no significant interaction effect of treatment, gender and achievement levels on the attitude of pupils towards Basic Science and Technology (BST). Recommendations were made which include that scaffolding instructional strategy should be used in classroom teaching/learning interaction to enhance the teaching and learning of pupils as well as improve their attitude towards Basic Science and Technology.